Financial Analysis of Dairy Cattle Farm on the Farming Company Level - Setiyawan, H; Santoso, SI; Mukson, Mukson (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
This research was conducted to evaluate the feasibility level of dairy cattle farm on the farming company level especially from the financial aspects. Research was carried out from March to July 2003 in Rumeksa Mekaring Sabda dairy cattle farm company, Argomulyo District, Salatiga. Case study was used as research method. Collected data was tabulated and analyzed using financial analysis criteria (Return On Investment, Payback Period, Net Present Value, Benefit Cost Ratio and Internal Rate of Return). The result showed that ROI (20.44%) is higher than deposit interestÂ rate (8%). The length of payback period (3 years and 6 months) is faster than maximum period that was predicted by the company (5 years). NPV (Rp. 45,565,585.16) and BC Ratio (1.42) have positive and higher value (more than 1), respectively. IRRâs value (38.45%) is higher than credit interest rate (18%). Based on the results, it can be concluded that the company is feasible enough to continue the operational project. (Animal Production 7(1): 40-45 (2005)Â Key Words : Financial analysis, farming company, dairy cattle